Healthcare professionals' understanding of the legislation governing research involving adults lacking mental capacity in England and Wales: a national survey. Issue 9 (25th April 2018) - Shepherd, Victoria; Griffith, Richard; Sheehan, Mark; Wood, Fiona; Hood, Kerenza
Abstract : Objective: To examine health and social care professionals' understanding of the legislation governing research involving adults lacking mental capacity in England and Wales. Methods: A cross-sectional online survey was conducted using a series of vignettes. Participants were asked to select the legally authorised decision-maker in each scenario and provide supporting reasons. Responses were compared with existing legal frameworks and analysed according to their level of concordance. Results: One hundred and twenty-seven professionals participated. Levels of discordance between responses and the legal frameworks were high across all five scenarios (76%–82%). Nearly half of the participants (46%) provided responses that were discordant in all scenarios. Only two participants (2%) provided concordant responses across all five scenarios. Discussion: Participants demonstrated a lack of knowledge about the legal frameworks, the locus of authority and the legal basis for decision-making. The findings raise concern about the accessibility of research for those who lack capacity, the ability to conduct research involving such groups and the impact on the evidence base for their care. Conclusion: This is the first study to examine health and social care professionals' knowledge and understanding of the dual legal frameworks in the UK. Health and social care professionals' understanding and attitudes towards research involving adults with incapacity may warrant further in-depth exploration. The findings from this survey suggest that greater training and education is required.